Enhanced Rate Capability of Oxide Coated Lithium Titanate within Extended Voltage Ranges - Ahn, Dongjoon; Xiao, Xingcheng (Frontiers in Energy Research, 2015)
Lithium titanate (Li4Ti5O12 or LTO) is a promising negative electrode material of high-power lithium-ion batteries, due to its superior rate capability and excellent capacity retention. However, the specific capacity of LTO is less than one half of that of graphite electrode. In this work, we applied ultrathin oxide coating on LTO by the atomic layer deposition technique, aiming for increasing the energy density by extending the cell voltage window and specific capacity of LTO. We demonstrated that a few nanometer thick Al2O3 coating can suppress the mechanical distortion of LTO cycled at low potential, which enable the higher specific capacity and excellent capacity retention. Furthermore, the surface coating can facilitate the charge transfer, leading to significantly improved rate capabilities, comparing with the uncoated LTO.